KAJIAN LITERATUR : EFEKTIVITAS ICE BREAKING DALAM PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Nurul Fa'izah; Shopia Nabila; Siti Nor Shahada; Wahdah Refia Rafianti; Ahmad Suriansyah; Rahmi Nur ‘Aini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the extent to which ice breaking activities are effective in improving learning motivation among elementary school students by reviewing findings from previous research. The method employed is a literature review, involving the selection and analysis of relevant research articles, academic reports, and publications from the past several years. The review indicates that ice breaking contributes to a more supportive classroom climate, enhances student engagement, and reduces fatigue during learning activities. Moreover, several studies highlight that structured implementation of ice breaking strengthens intrinsic motivation and improves students’ emotional readiness to absorb instructional content. These findings suggest that ice breaking can serve as a complementary strategy to support learning in elementary education.